2014
DOI: 10.1021/es500827v
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation of Octachloronaphthalene over As-Prepared Fe3O4 Micro/Nanomaterial and Its Hypothesized Mechanism

Abstract: Decomposition of octachloronaphthalene (CN-75) featuring fully substituted chlorines was investigated over asprepared Fe 3 O 4 micro/nanomaterial at 300°C. It conforms to pseudo-first-order kinetics with k obs = 0.10 min −1 as comparable to that of hexachlorobenzene and decachlorobiphenyl. Analysis of the products indicates that the degradation of CN-75 proceeds via two competitive hydrodechlorination and oxidation pathways. The onset of hydrodechlorination producing lower chlorinated naphthalenes (CNs) is mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 37 publications
0
35
1
Order By: Relevance
“…(2) where k obs is the pseudo-first-order initial rate constant (min −1 ), as calculated from the experimental data. The pseudo-first-order rate constant for the degradation of PCB-209 over 1%Ca-Fe 2 O 3 was 0.103 min −1 (R 2 = 0.94), which was comparable with that of PCN-75 degradation over the prepared Fe 3 O 4 , with pseudo-first-order rate constant of 0.10 min −1 (R 2 = 0.89) (Su et al, 2014). The existence of strong π -conjugated effects both in PCB-209 and PCN-75 resulted in their similar reaction rate constants.…”
Section: Characterizations Of Ca Species-doped Fe 2 Omentioning
confidence: 55%
See 4 more Smart Citations
“…(2) where k obs is the pseudo-first-order initial rate constant (min −1 ), as calculated from the experimental data. The pseudo-first-order rate constant for the degradation of PCB-209 over 1%Ca-Fe 2 O 3 was 0.103 min −1 (R 2 = 0.94), which was comparable with that of PCN-75 degradation over the prepared Fe 3 O 4 , with pseudo-first-order rate constant of 0.10 min −1 (R 2 = 0.89) (Su et al, 2014). The existence of strong π -conjugated effects both in PCB-209 and PCN-75 resulted in their similar reaction rate constants.…”
Section: Characterizations Of Ca Species-doped Fe 2 Omentioning
confidence: 55%
“…The driving force of PCB hydrodechlorination reaction during different steps was discussed on the basis of the isomer distribution pattern in combination with thermodynamic data and steric effect. The results generated in the present study were compared with those obtained from PCN-75 degradation reported in our previous work under similar reaction conditions (Su et al, 2014).…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations